Cost efficiency of inpatient rehabilitation following acquired brain injury: the first international adaptation of the UK approach - Ian D Cameron; Julie Ratcliffe; Ian Cameron; Belinda Gabbe; Rachel Milte; Ciara Ryan; Karen Roberts; Zhibin Chen; Russell Gruen; Laura Jolliffe; Natasha A Lannin; Peter Hunter; et al. (BMJ Open)
Objectives To adapt and apply a model for evaluating the functional benefits and cost efficiency of specialist inpatient rehabilitation to the Australian context, comparing functional outcomes and savings in the cost of ongoing care after acquired brain injury.Design An observational cohort analysis of prospectively collected clinical data from admission to discharge, with follow-up to 3 years.Setting A newly established state-wide inpatient postacute rehabilitation unit in Victoria, Australia for patients with moderate to severe acquired brain injury.Participants This study included consecutive patients admitted to the programme during its first 2 years’ operation (January 2016 to December 2017). Inclusion criteria consisted of complete outcome measures recorded on admission and discharge, total n=196, mean age 44.6 years (range 17–78), males:females 72:28%, aetiology:trauma n=124 (63%), stroke n=42 (21%), diffuse n=18 (9%) and other-mixed n=12 (7%).Interventions Specialist inpatient multidisciplinary rehabilitation.Outcome measures Dependency and care costs: Northwick Park Dependency Scale/Care Needs Assessment (NPCNA); Functional independence: UK Functional Assessment Measure. Cost efficiency: (a) Time is taken to offset rehabilitation costs by savings in NPCNA-estimated costs of ongoing care and (b) net projected lifetime savings.Results Median length of stay 75 (IQR: 33.5–169.5) days, mean episode costs were $A147 044 (95% CI $A126 436, $A167 652). There was a significant reduction in dependency between admission and discharge on all measures (Holm-Bonferroni corrected p<0.001) which was sustained at follow-up in those traced at 1–3 years. Savings were greatest in the highest-dependency group. Estimated mean overall reduction in ‘weekly care costs’ was $A7206, offsetting the cost of rehabilitation within 5.53 months (95% CI 2.27, 8.78). Mean projected net lifetime savings were $A13.4 million (95% CI $A11.4, $A15.4) per patient.Conclusions This study provides proof of principle for use of the NPCNA cost-efficiency model outside the UK and yields further evidence that rehabilitation for patients with complex disabilities represents value for money. For every dollar spent on inpatient rehabilitation in this cohort, an estimated $A91 was saved in ongoing care costs.